Evaluasi Sistem Informasi Dapodik Pada SDN 023 Penajam Paser Utara Mengunakan Metode Usability Testing - Anisa Nur Fitriah; Elvin Leander Hadisaputro; Erlin Setyaningsih (JURIKOM (Jurnal Riset Komputer), 2022)
The Basic Education Data Application or Dapodik is an integrated National-scale data collection system, and is the main data source for National Education, which is part of the national education planning program in realizing intelligent and competitive Indonesian people. To find out how far effective and efficient the system is, it is necessary to evaluate. The evaluation carried out in this study used usability testing using five categories, namely learnability, memorability, efficiency, errors, and satisfaction. The five indicators were represented in the form of a questionnaire statement and distributed online to Dapodik application users. The total sample of respondents is a total of 14 people consisting of principals, teachers, administrative staff, library staff and school operators. The test method used in this study includes a validity test consisting of a reliability test and a correlation test. The significance of the Alpha value used in this study is 0.05. From the results of the data validity test, all indicators have a value above 0.05. From the results of the reliability test, all statements in the questionnaire also have a Cronbach's Alpha value of 0.489, which means that all statements are appropriate. The evaluation results show that of the five indicators in the dapodik application, the highest value for the error indicator is 5.19, this means that the dapodik application user does not experience errors/damages when using the dapodik application. Meanwhile, the lowest value of the five indicators is memorability of 4.26 which is in the very good indicator, which means that it is said that users can easily remember and know the use of the dapodik application